Minimal Incision Scar-Less Open Umbilical Hernia Repair in Adults – Technical Aspects and Short-Term Results - Zachariah, Sanoop K.; Kolathur, Najeeb Mohamed; Balakrishnan, Mahesh; Parakkadath, Arun Joseph (Frontiers in Surgery, 2014)
Background: There is no gold standard technique for umbilical hernia repair .Conventional open umbilical hernia repair often produces an undesirable scar. Laparoscopic umbilical hernia repair requires multiple incisions beyond the umbilicus, specialized equipments, and expensive tissue separating mesh. We describe our technique of open umbilical hernia repair utilizing a small incision. The technique was derived from our experience with single incision laparoscopy. We report the technical details and short term results. Methods: This is a retrospective analysis of the first 20 patients who underwent minimal incision scar-less open umbilical hernia repair, from June 2011 to February 2014. A single intra-umbilical curved incision was used to gain access to the hernia sac. Primary suture repair was performed for defects upto 2cm.Larger defects were repaired using an onlay mesh. In patients with a BMI of 30 kg/m2 or greater, onlay mesh hernioplasty was performed irrespective of the defect size. Results: A total of 20 patients, 12 males and 8 females underwent the procedure. Mean age was 50 (range 29 - 82) years. Mean BMI was 26.27 (range 20. -33.1) kg/m2. Average size of the incision was 1.96 range (1.5 to 2.5) cm. Mesh hernioplasty was done in 9 patients. 11 patients underwent primary suture repair alone. There were no postoperative complications associated with his technique. Average post operative length of hospital stay was 3.9 (range 2-10) days. Mean follow-up was 29.94 months, (2 weeks to 2.78 years). On follow up there was no externally visible scar in any of the patients. There were no recurrences on final follow up. Conclusion: This technique provides a similar cosmetic effect as obtained from single port laparoscopy. It is easy to perform safe, offers good cosmesis, does not require incisions beyond the umbilicus and cost effective, with encouraging results on short term follow up. Further research is needed to assess the true potential of the technique and